2010
DOI: 10.1152/ajpgi.00429.2009
|View full text |Cite
|
Sign up to set email alerts
|

Fasting-induced intestinal apoptosis is mediated by inducible nitric oxide synthase and interferon-γ in rat

Abstract: Ito J, Uchida H, Yokote T, Ohtake K, Kobayashi J. Fastinginduced intestinal apoptosis is mediated by inducible nitric oxide synthase and interferon-␥ in rat. Am J Physiol Gastrointest Liver Physiol 298: G916 -G926, 2010. First published April 8, 2010 doi:10.1152/ajpgi.00429.2009 is associated with intestinal apoptosis in health and disease. This study aimed to investigate the role of intestinal NO in the regulation of apoptosis during fasting in rats. Male Wistar rats were divided into two groups and subcutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 56 publications
4
33
1
1
Order By: Relevance
“…In the advanced tubular intestine of tetrapods (e.g., mammals, chicken and reptiles) [20][21][22][23][24][25][26] , similar localizations of apoptotic or proliferating cells in the epithelia have been reported, whereas proliferating cells in fresh water and apoptotic cells in seawater were observed throughout the intestinal epithelia of euryhaline teleosts [15,27] . Furthermore, the degree of cell proliferation and apoptosis were modified in both intestinal epithelia of the shark and the murines by fasting/feeding, but in opposite directions [5,6,28,29] . Whereas a reversible decrease in the epithelial apoptosis and cell proliferation are observed in the shark during fasting, epithelial cell turnover is induced in the murine intestinal mucosa after fasting [6,28,29] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the advanced tubular intestine of tetrapods (e.g., mammals, chicken and reptiles) [20][21][22][23][24][25][26] , similar localizations of apoptotic or proliferating cells in the epithelia have been reported, whereas proliferating cells in fresh water and apoptotic cells in seawater were observed throughout the intestinal epithelia of euryhaline teleosts [15,27] . Furthermore, the degree of cell proliferation and apoptosis were modified in both intestinal epithelia of the shark and the murines by fasting/feeding, but in opposite directions [5,6,28,29] . Whereas a reversible decrease in the epithelial apoptosis and cell proliferation are observed in the shark during fasting, epithelial cell turnover is induced in the murine intestinal mucosa after fasting [6,28,29] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the degree of cell proliferation and apoptosis were modified in both intestinal epithelia of the shark and the murines by fasting/feeding, but in opposite directions [5,6,28,29] . Whereas a reversible decrease in the epithelial apoptosis and cell proliferation are observed in the shark during fasting, epithelial cell turnover is induced in the murine intestinal mucosa after fasting [6,28,29] . This difference may reflect the differing feeding ecology of sharks most of which, unlike murines, tend to eat large meals at irregular intervals [30,31] .…”
Section: Discussionmentioning
confidence: 99%
“…To measure enterocyte apoptosis in the jejunum, the apoptotic index (AI) was calculated by conventional light microscopy of H&E-stained specimens, following the methods of Dahly et al and Ito et al 6,9 Terminal deoxynucleotidyl transferase dUTP nick-end labelling (TUNEL) staining of apoptotic cells is easy to interpret for all images; however, because of its nonspecific staining, representative apoptotic changes were utilized for the analysis of AI. In brief, jejunal sections as used above for histopathological analysis were examined in a blinded manner for the typical attributes of apoptotic cells.…”
Section: Collection Of Intestinal Mucosamentioning
confidence: 99%
“…For instance, rat small intestines with histological abnormalities demonstrate increased iNOS expression. 9,12 nNOS is the predominant isoform in the intestine, and its activity is inversely correlated with the extent of tissue injury. 13 Previous investigations using animal models have suggested that nNOS and iNOS are key in the development and progression of post-inflammatory functional gastrointestinal disorders, 14 ischemia-reperfusion injury (IRI), acute rejection (AR) in intestinal transplantation, 15 and necrotizing enterocolitis (NEC).…”
Section: Introductionmentioning
confidence: 99%
“…It is known that the homeostasis of the intestinal apoptotic system is sensitive to enteral nutrient intake . Thus, the apoptotic process can be quickly initiated if enteral nutrient intake is insufficient, which can in turn lead to intestinal atrophy (Niinikoski et al, 2004;Ito et al, 2010;Dodge et al, 2012). However, it remains unclear whether such nutrientintake-level-dependent regulation of the development of the small intestine exists in IUGR neonates.…”
Section: Introductionmentioning
confidence: 99%